(untitled) (Global Journal of Human-Social Science, 2018)
This study was carried out in Ekiti State Nigeria to examine the savings avenue of women cassava processors; determine factors affecting their propensity to save and analyze the determinants of savings. Information was gathered from a total of 180 women cassava processors through a wellstructured questionnaire. A multi-stage random sampling procedure was adopted in the selection of respondents. The analytical tools employed were descriptive statistics, Friedman ranking analysis, multiple regressions, and Pearson correlation analysis. Findings showed that the mean annual income and savings of respondents were ₦488,750 and ₦121,180 respectively with Marginal Propensity to save (MPS) at 0.254. The MPS of the respondents for every income generated was ₦0.254. The regression coefficients showed that age, level of education, household size, annual income, and quantity of Garri processed were the determinants of savings of the respondents. The study showed that saving potential existed among the women cassava processors in the study area. Findings recommend that government should subsidize modern cassava processing facilities to reduce processing cost and increase the income of the processors.